Bare life production and the author's criticism in the short story "Manuel" by Seno Gumira Ajidarma: the study of agambenâ€™s sociology of literature - Ilham Rabbani; Aprinus Salam (BAHASTRA, 2021)
The short story â€œManuelâ€ written by Seno Gumira Ajidarma set in the Santa Cruz incident in Dili (1991), raised humanitarian issues in the relation to state power. East Timor citizens lost their human rights because of the Indonesian military invasion of their territory, and were in a homo sacer or bare life situation. Â This research uses the theory of political philosophy developed by Giorgio Agamben. The method used is descriptive qualitative. The research questions that are trying to be answered: first, how does the state impose the state of exception so that it raises bare life in short story â€œManuel?â€; and second, how does the author form of criticism through the short story â€œManuel?â€ towards the New Order citizenship politics? The finding of this study are: first, First, the motive for the application of the state of exception is using the pretext of integration, anticipation of communism, development, and agreements related to the exploration of Timor Gap; and secondly, criticism of the state was conveyed through the speeches of the figure of Manuel, borrowing the speech of East Timor activists, and the adoption of discourse of resistance to the Indonesia military. However, this strategy has an impact on the originality of criticism which deserves to be questioned again.